Pengolahan Data Keuangan Pada PT. Mugan Kreasi Indonesia - Sri Muryani; Khairani Syahri Putri Kencono (Artikel Ilmiah Sistem Informasi Akuntansi, 2021)
Mugan Kreasi Indonesia is a company engaged in retail sales. PT. Mugan Kreasi Indonesia or known as Mugan Home sells household appliances, kitchen utensils, beauty products, mother and baby equipment, medical equipment, mobile phone accessories, vehicle parts and accessories. Data collection methods used in obtaining data to complete this research are interviews, observations, and literature study. Processing of financial data that occurs in this company where the recording of initial transactions to financial statements. still done manually. This allows errors in recording financial data and loss of transaction evidence. To overcome the existing problems, data processing is carried out using an accounting application. By applying the Zahir Accounting application, it has met computerized financial accounting standards is the best solution in solving problems that occur at PT. Mugan Creative Indonesia. It is expected that data processing, both input and output, can run well, quickly, and precisely. Financial reports can be presented on time so that leaders can analyze the company's finances.